Rural-urban disparity in uptaking skilled antenatal care visits by pregnant women in Bangladesh: Zero and One Inflated Poisson regression model. - Lubana Tanvia; M Ershadul Haque; Wasimul Bari (PLoS ONE)
Background Utilization of maternal health care services, specifically, antenatal care services from skilled health providers have been given utmost priority in low- and middle-income countries over years with a view of mitigating complications during pregnancy as well as safeguarding the health and survival of both mother and newborn. However, there is a general tendency of pregnant mothers in Bangladesh of receiving skilled antenatal care (SANC) service once, or even never which refrains us to ensure World Health Organization (WHO) recommended eight plus SANC visits, additionally, to meet Sustainable Development Goal (SDG) number three. Objectives The study aims at assessing how the average number of SANC visits taken by the reproductive women in Bangladesh changes over the time in rural and urban areas together with finding out the potential demographic and socio-economic factors associated with SANC visits by addressing possible accumulation of zero and one counts in SANC visits. Methods In this study, data have been retrieved from last four waves of Bangladesh Demographic and Health Surveys ranging from 2011 to 2022 and later combined together to form a pooled dataset. Non-parametric Kruskal-Wallis test has been performed for exploring unadjusted association of covariates with the response and Mann-Whitney U test has been conducted for multiple comparison in case of significant association for a covariate having more than two categories. For checking the existence of concurrent inflation at zero and one in the pooled dataset, partial score test has been performed. Based on the results of score test, Zero and One Inflated Poisson regression model has been fitted to the pooled dataset, where an interaction term between area of residence and survey year has been considered for trend analysis. Results The study highlights that the rate of mean SANC visits is rapidly rising with time among pregnant women not only from the urban areas but also from the rural areas of Bangladesh. However, the rate of change in uptaking the SANC visits is higher in rural area compared to urban area. It was observed that for a given survey year, the rate of mean SANC visits was higher among women from urban areas compared to that among women from rural areas of Bangladesh. This study provides the evidence of 17.2% extra zero counts and 1.1% extra one counts in the pooled dataset. Conclusion The study results depict that inequity in SANC services based on area of residence prevails in Bangladesh. However, the gap in the rate of mean SANC visits in rural areas compared to urban areas has gradually reduced over time. Based on the results, the study comes up with some recommendations to facilitate the policy makers in improvising strategies and ensuring sustainable rise in SANC counts as well as WHO recommended positive pregnancy experience in the country to meet SDGs.